2022
DOI: 10.3390/v14122651
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray Tomography Reveals HSV-1-Induced Remodeling of Human B Cells

Abstract: Upon infection, viruses hijack the cell machinery and remodel host cell structures to utilize them for viral proliferation. Since viruses are about a thousand times smaller than their host cells, imaging virus-host interactions at high spatial resolution is like looking for a needle in a haystack. Scouting gross cellular changes with fluorescent microscopy is only possible for well-established viruses, where fluorescent tagging is developed. Soft X-ray tomography (SXT) offers 3D imaging of entire cells without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…After generating and characterising the mutants, defects in virus assembly were explored with high- resolution imaging techniques under cryogenic conditions. Cryogenic imaging using soft-X-ray tomography captures the ultrastructure of the cell in 3D and has the advantage of allowing the study of samples in a near-native state without the need for chemical fixation 26,50 . U2OS osteosarcoma cells were used in this study because they have been used for ultrastructural HSV-1 research and have been demonstrated to be durable under X-ray exposure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After generating and characterising the mutants, defects in virus assembly were explored with high- resolution imaging techniques under cryogenic conditions. Cryogenic imaging using soft-X-ray tomography captures the ultrastructure of the cell in 3D and has the advantage of allowing the study of samples in a near-native state without the need for chemical fixation 26,50 . U2OS osteosarcoma cells were used in this study because they have been used for ultrastructural HSV-1 research and have been demonstrated to be durable under X-ray exposure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to T cells, HSV-1 infection in human B cells has been investigated in a previous study. The research found that several cellular structures of B cells, such as cytoplasmic stress granules and multivesicular structures, were changed during HSV-1 infection (Chen et al, 2022). Nevertheless, there was no data about HSV-1 inducing actin polymerization and filopodia formation in B cells.…”
Section: Hsv Entry Into T Lymphocytesmentioning
confidence: 98%
“…[ 4–10 ] Because of these unique characteristics, SXT has been recently used in a wide range of applications, from phenotyping of cells such as bacteria, yeast, and advanced eukaryotes [ 11–16 ] to investigating cell–nanoparticle, [ 17,18 ] cell–parasite, [ 19–21 ] and cell–virus interactions. [ 22–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Because of these unique characteristics, SXT has been recently used in a wide range of applications, from phenotyping of cells such as bacteria, yeast, and advanced eukaryotes [11][12][13][14][15][16] to investigating cellnanoparticle, [17,18] cell-parasite, [19][20][21] and cell-virus interactions. [22][23][24][25][26][27][28] SXT is suitable for imaging of a wide variety of cell types. However, some investigators have reported that soft X-ray imaging is limited to specimens less than 10 μm thick.…”
Section: Introductionmentioning
confidence: 99%